PP.37.14: AMBULATORY BLOOD PRESSURE MONITORING AS A SCREENING METHOD FOR OBSTRUCTIVE SLEEP APNEA SYNDROME. (June 2015) - Stojanovic, M.; Vujovic, S.; Gajic, M. Tancic; Ivovic, M.; Marina, L.J.; Nisic, T.; Beleslin, B.; Stojkovic, M.; Savic, S.; Lalic, T.; Barac, B.; Barac, M.; et al.
Abstract : Objective: Obstructive sleep apnea (OSAS) is a risk factor for cardiovascular disease. In everyday practice OSAS is not recognized very often and the person is not advised to do polysomnography or sleep study. In 70 percent overweight people studies revealed OSAS and in 80 percent of people with OSAS hypertension has been found. Obstructive sleep apnea is one of the causes of hypertension and changes the circadian rhythm of blood pressure by increasing blood pressure during sleep. Design and method: ABPM and sleep study was done in 156 persons of average body mass index of 38 kg/m2. Results: Analysis of monitoring of blood pressure revealed 112 persons with higher blood pressure during sleep compared to the values before and after a period of sleep and 44 persons have equal values of blood pressure during daily activities and sleep. Sleep study diagnosed 110 people with severe and 12 persons with moderate OSAS. Conclusions: Monitoring of blood pressure with a high probability indicates the existence of obstructive sleep apnea syndrome on the basis of altered circadian rhythm and can be used as a screening method that is more accessible than polysomnography.